2002
DOI: 10.1117/12.481652
|View full text |Cite
|
Sign up to set email alerts
|

Contamination control of the SABER cryogenic infrared telescope

Abstract: The SABER instrument (Sounding of the Atmosphere using Broadband Emission Spectroscopy) is a cryogenic infrared sensor on the TIMED spacecraft with stringent molecular and particulate contamination control requirements. The sensor measures infrared emissions from atmospheric constituents in the earth limb at altitudes ranging from 60 to 180 km using radiatively-cooled 240 K optics and a mechanicallyrefrigerated 75 K detector. The stray light performance requirements necessitate nearly pristine foreoptics. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This program has been a useful tool not only to determine acceptable contaminant levels for contaminantion control plans, but has also been used to identify the cause for signal loss. These program has been useful for IR instruments at SDL including SABER (Sounding of the Atmosphere using Broadband Emission Spectroscopy) 7 and others.…”
Section: Introductionmentioning
confidence: 99%
“…This program has been a useful tool not only to determine acceptable contaminant levels for contaminantion control plans, but has also been used to identify the cause for signal loss. These program has been useful for IR instruments at SDL including SABER (Sounding of the Atmosphere using Broadband Emission Spectroscopy) 7 and others.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce vulnerability to water outgassing and to control particulate redistribution and contamination within the FPA (which is not hermetically sealed) SABER was designed with an optimized purge and vent system (Dyer et al., 2002) as shown in Figure 9. The purge system maintained the cleanliness and optical quality for those times when SABER was not being operated or stored in vacuum.…”
Section: The Saber Instrumentmentioning
confidence: 99%
“…To reduce vulnerability to water outgassing and to control particulate redistribution and contamination within the detector assembly (which is not hermetically sealed) SABER was designed with an optimized purge and vent system (Dyer et al, 2002) as shown in Figure 9. The purge system maintained the cleanliness and optical quality for those times when SABER was not being operated under or stored in vacuum.…”
Section: Saber Purge and Vent Systemmentioning
confidence: 99%